2018
DOI: 10.1002/cam4.1479
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiotherapy and chemotherapy improve survival in patients with pancreatic adenocarcinoma receiving surgery: adjuvant chemotherapy alone is insufficient in the era of intensity modulation radiation therapy

Abstract: In the era of intensity modulation radiation therapy (IMRT), no prospective randomized trial has evaluated the efficacy of adjuvant therapies such as adjuvant concurrent chemoradiotherapy (CCRT), adjuvant sequential chemotherapy and radiotherapy (CT‐RT), and adjuvant CT alone in resectable pancreatic adenocarcinoma (PA). Through propensity score matching, we designed a nationwide, population‐based, head‐to‐head cohort study to determine the effects of dissimilar adjuvant treatments on resectable PA. We minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…2 Others reported that a combination of CTx and radiotherapy was the most significant positive prognostic factor for survival. 5,26,27 In this study, we had 4.3% perioperative mortality which is nearly similar to what was reported in other studies. 2,4,6,13,21,28 Seppänen et al, reported perioperative mortality 2.1%, and 5-year survival 22% after PD for PDAC.…”
Section: Discussionsupporting
confidence: 90%
“…2 Others reported that a combination of CTx and radiotherapy was the most significant positive prognostic factor for survival. 5,26,27 In this study, we had 4.3% perioperative mortality which is nearly similar to what was reported in other studies. 2,4,6,13,21,28 Seppänen et al, reported perioperative mortality 2.1%, and 5-year survival 22% after PD for PDAC.…”
Section: Discussionsupporting
confidence: 90%
“…PSM has been widely used in several areas of medical research including studies to assess factors associated with cancer survival 25, 26, 27, 28, 29. In our study, after 1:1 matching, married patients showed survival advantage over unmarried patients.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate preoperative differentiation between pNET and PDAC is crucial not only for selecting more suitable treatment but patient prognosis . For pNET patients, previous studies have reported that more aggressive surgery method could lead to higher morbidity and did not significantly improve overall survival compared with conservative resections .…”
Section: Introductionmentioning
confidence: 99%